Infrared spectra of methyl isocyanate isolated in Ar, Xe and N2 matrices - Reva, Igor (2010)
The infrared spectra of methyl isocyanate monomer isolated in cryogenic argon, xenon and nitrogen matrices were studied. Interpretation of the experimental results was supported by harmonic and anharmonic calculations carried out at the DFT, MP2 and CCSD levels of approximation. Spectral indicators of the molecule structural flexibility were examined, the most striking of these being the multiplet structure of the most intense infrared band due to the antisymmetric stretching vibration of the NCO group. The observed quadruplet, spanning over the frequency range of nearly 100 cm−1, between 2350 and 2250 cm−1, was interpreted in terms of coupling with the low frequency torsion of the methyl group.